Numerical Investigation of Reinforced Concrete Beams with Rectangular Spiral Reinforcement in Torsion - Moosa Mazloom (Iranian Society of Structrual Engineering (ISSE), 2019)
In this numerical investigation, rectangular spiral reinforcement behavior have been examined. This article presents the finite element models of the experimental tests of 27 reinforced concrete beams that have rectangular spiral reinforcement with the distance of different vertical and horizontal leg angles. The explicit analyses have been verified the condition of confinement by changing in stress-strain curve of the reinforced concrete beams. According to the results of modeling, increasing the transverse reinforcement and improving in confinement advances the maximum torsion and more ductility of the concrete beams. Using continues rectangular spiral reinforcement in comparison with commonly used stirrups, with the same percentage of transverse reinforcement, improved the maximum torsion capacity from 5 to35%. In rectangular spiral reinforcement with various top angles, and the same percentage of the transverse reinforcement, increasing the top and side angles improves the maximum torsion. This improvement in torsion capacity is for the top angle of up to 20 degree. Exploring the results of rectangular spiral reinforcement that their top angles are not zero indicates that for the angles less than 14 degree, the results of maximum torsion have little deference with the ones having no top angle. Therefore, using rectangular spiral reinforcement with zero top angle is recommended. Its simple manufacturing and decreasing the cost of producing is considerable too.